1999
DOI: 10.1111/j.1751-1097.1999.tb07979.x
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomes Are Sites of Fluoroquinolone Photosensitization in Human Skin Fibroblasts: A Microspectrofluorometric Approach*

Abstract: The fluoroquinolone antibiotics are widely used despite their strong phototoxicity under solar UV irradiation. Although they are known as good photodynamic photosensitizers, other factors than production of activated oxygen species may play a role in the effectiveness of the phototoxic effect. Subcellular localization is one of the important parameters that may determine this strength. Using microspectrofluorometry, it is shown that norfloxacin, ofloxacin, lomefloxacin, ciproflaxin and BAYy3118 are readily inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 16 publications
3
31
0
Order By: Relevance
“…These data are in good agreement with the data reported by Wagai and Tawara [6] [7], who have demonstrated that the phototoxicity associated with quinolones in balb/c mice was initiated by the generation of ROS in the target tissue, which specifically involved hydroxyl radical, as well superoxide anion and hydrogen peroxide. Moreover, it has also been reported that the initial steps in the quinolone phototoxicity probably involve hydroxyl-radical attack on the cell membrane and mitochondria [32]. In this context, we have demonstrated a gradual loss of the mitochondrial potential (Dy m ) for LVX and OFX, suggesting that the mitochondria are readily damaged by photosensitization with these fluoroquinolones.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…These data are in good agreement with the data reported by Wagai and Tawara [6] [7], who have demonstrated that the phototoxicity associated with quinolones in balb/c mice was initiated by the generation of ROS in the target tissue, which specifically involved hydroxyl radical, as well superoxide anion and hydrogen peroxide. Moreover, it has also been reported that the initial steps in the quinolone phototoxicity probably involve hydroxyl-radical attack on the cell membrane and mitochondria [32]. In this context, we have demonstrated a gradual loss of the mitochondrial potential (Dy m ) for LVX and OFX, suggesting that the mitochondria are readily damaged by photosensitization with these fluoroquinolones.…”
mentioning
confidence: 82%
“…As recently demonstrated [19], lysosomes are major sites of localization of fluoroquinolones although other subcellular organelles can also be the target of fluoroquinolones. In fact, we also found that, upon fluoroquinolone addition, fluorescence in 3T3 cells was partially localized in mitochondria (data not shown), and co-localized with that of TMRM, a lipophilic cation commonly used for the assessment of the mitochondrial potential (Dy m ) [20] [21].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Lysosomal alterations can be involved in cell death caused by many photosensitizers such as certain fluoroquinolones, [20] acri- dine orange, [21] and some psoralen analogues. [7] To investigate the integrity of lysosomes after irradiation in the presence of 11 f and 11 g, flow cytometric analysis was performed with the fluorescent dye acridine orange (AO).…”
Section: Evaluation Of Lysosome Involvement In Cell Deathmentioning
confidence: 99%
“…Santus’ group had earlier demonstrated that lysosomal photodamage mediated by fluoroquinolones could lead to impaired endocytosis 10,11. It was proposed that this result derived from release of lysosomal proteases into the cytoplasm, since the irreversible cysteine-protease inhibitor E64d prevented the impairment.…”
Section: Introductionmentioning
confidence: 99%